Knowledge regarding neonatal resuscitation among nurses in a municipality hospital: A cross-sectional study - Singh, Ajanta Maharajan; Shrestha, Bikash; Kaiti, Kusum Shrestha; Singh, Shreejana Singh; Shrestha, Gentle Sunder (Bangladesh Critical Care Journal, 2023)
Background: Neonatal resuscitation (NR) is a means to restore life of a baby from the state of asphyxia. It is a single most important intervention for neonates with birth asphyxia. Resuscitation in neonates is more challenging than that of an adult or even an older infant or child. Poor resuscitation techniques can contribute to poor outcome in neonates with birth asphyxia. Nurses being the front-liners to receive the newborn babies, level of knowledge about NR among them can affect the outcome in these patients. Objectives: This study was aimed to assess the level of knowledge regarding neonatal resuscitation among the nurses. Methodology: The study was conducted among the nurses of one of the municipality hospitals of Nepal by using structured self-administered questionnaires and total enumeration sampling method was used. A total of 56 responses were obtained. Results: Among 56respondents, 51 (94.6%) were in the age group of 20-29 years. Majority of them 52 (92.8%) had inadequate knowledge about neonatal resuscitation and only 4 (7.2%) had adequate knowledge. Conclusions: Majority of the nurses have inadequate knowledge regarding neonatal resuscitation. Training and educational programs for nurses and on neonatal resuscitation can be helpful Bangladesh Crit Care J March 2023; 11 (1): 9-12